FACTORS AFFECTING BUS DWELL TIME AT INTERMEDIATE STOPS - Rakhmonov Azimjon; Bakhriddinov Dostonbek (Zamonaviy ilmiy yondashuvlar va texnologik taraqqiyotning ustuvor yo‘nalishlari, 2026)
This article provides a scientific analysis of the key factors affecting bus dwell time at intermediate stops in urban environments. Factors such as passenger flow intensity, door design, driver behavior, stop infrastructure, and weather conditions have been studied. Based on the analysis results, practical recommendations for optimizing dwell time have been developed. The research is aimed at improving the efficiency of public transport management for cities in Uzbekistan.